How to quantify Varroa destructor in honey bee (Apis mellifera L.) colonies - Cameron Jack; Nathan Sperry; Ashley N. Mortensen; Jamie Ellis (EDIS)
The Varroa destructor mite, a devastating pest of western honey bees, can threaten a honey bee colony’s survival if it is left uncontrolled. This 8-page fact sheet written by Cameron Jack, Nathan Sperry, Ashley N. Mortensen, and Jamie Ellis and published by the UF/IFAS Entomology and Nematology Department explains how to monitor honey bee colonies to ensure that infestations of these destructive pests do not grow to dangerous levels. https://edis.ifas.ufl.edu/in1257